Three's a crowd: the process of triadic translation in a South African psychiatric institution - Slabbert, Meggan (Rhodes University, Faculty of Humanities, Department of Psychology, 2010)
Mental health care in South Africa has long been governed by inequalities (Foster & Swartz, 1997). During apartheid, those who did not speak English and Afrikaans could not access mental health services in the same way as those who did (Foster & Swartz, 1997). One main reason for this is the majority of mental health practitioners could not, and were not required to speak languages other than English and Afrikaans (Swartz, 1991). The South African mental health literature suggests that language and communication must be prioritised if there is to be an improvement in mental health care services for those individuals who do not speak English and Afrikaans (Bantjes, 1999; Drennan & Swartz, 1999; Swartz & Drennan, 2000; Swartz & MacGregor, 2002). Drawing on Prasad's (2002) interpretation of Gadamer's critical hermeneutic theory and utilising thematic networks analysis (Attride-Stirling, 2001), this study investigated the process of translated clinical assessment interviews within a psychiatric hospital in the Eastern Cape Province within South Africa. Results of the study revealed that contextual factors, issues concerning linguistic and cultural heritage, clinicians' role expectations regarding translators' role performance, as well as relational dynamics regarding individual levels of control and influence within the translation triad, all impacted on the effectiveness of communication, translation and service provision. These fmdings are supported by literature on the theory and practice of translation that identifies these issues as prominent (Robinson, 2003). Specific recommendations regarding the formalisation of translation practices within the hospital setting, as well as the familiari~ation of clinical practitioners and psychiatric nurses with the intricacies of translation processes are offered.
Keywords: Mental health services -- South Africa -- Eastern Cape; Psychiatric hospitals -- South Africa -- Eastern Cape; Translating and interpreting -- Psychological aspects; Translating and interpreting -- Social aspects; Content analysis (Communication); South Africa -- Languages -- Translating and interpreting; Intercultural communication -- South Africa -- Eastern Cape; Culture conflict -- South Africa -- Eastern Cape; Communication and culture -- South Africa -- Eastern Cape; Physician and patient -- South Africa -- Eastern Cape; Communication in medicine -- South Africa -- Eastern Cape